Respuesta :

Answer:

The correct option is;

b. y = x², [tex]y = \left | x \right |[/tex]

Step-by-step explanation:

The equations are

1) y = x

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )=-\infty[/tex]

2) y = x²

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )=+\infty[/tex]

3) y = x³

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )=-\infty[/tex]

4) [tex]y = \left | x \right |[/tex]

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )=+\infty[/tex]

5) y = 1/x

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )=0[/tex]

6) y = eˣ

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )\rightarrow 0[/tex]

7) y = √x

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )= \infty\sqrt{(-1)}[/tex]

8) y = ㏑x

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )= \infty\sqrt{(-1)}[/tex]

9) y = sin x

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )=[/tex] undefined

10) y = cos x

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )=[/tex] undefined

11) y int (x)

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )=-\infty[/tex]

12) [tex]y = \dfrac{1}{1 + e^{-x}}[/tex]

[tex]\lim_{x\rightarrow -\infty }f\left (x \right )=0[/tex]

Therefore, the correct options are y = x² and [tex]y = \left | x \right |[/tex]

ACCESS MORE